Analisis Komparatif Abnormal Return, Trading Volume Activity dan Bid Ask Spread Terhadap Pelantikan Menteri BUMN Erick Thohir Pada IDX BUMN20 - Ni Luh Putu Ika Baktyarina; I Gusti Ayu Purnamawati (Ekuitas: Jurnal Pendidikan Ekonomi, 2020)
This study aimed at determining the difference in the average of abnormal return, trading volume activity and bid-ask spread before and after the turnover of BUMN Minister on a company registered in the the BUMN20 index. The type of data used in this study was secondary data employing the data collection technique of documentation method. The determination of samples in this study employed a purposive sampling method through certain criteria so as to obtain 20 samples. The analysis techniques employed in this study were paired sample t-test with the observation period of 10 days. The results of this study indicated that: (1) There was no average difference in the abnormal return before and after the turnover of BUMN Minister Erick Thohir; (2) There was no average difference in the trading volume activity before and after the turnover of BUMN Minister Erick Thohir; (3) There was no average difference on bid-ask spread before and after the turnover of BUMN Minister Erick Thohir.